The Application of a Sequence Alignment Method to the Creation of Typologies of Tourist Activity in Time and Space. (February 2015) - Shoval, Noam; McKercher, Bob; Birenboim, Amit; Ng, Erica
In this article we introduce the method of sequence alignment and its uses for creating tourist typologies based on temporal and spatial movements through a destination. The sequence alignment method was first developed in the 1980s by biochemists who wished to analyse DNA sequences; it was adapted for use in the social sciences towards the end of the 1990s. Unlike traditional quantitative methods, sequence alignment is concerned with the order (or sequence) of events. Thus, it is well suited for tourism research, as tourism involves the mobility of tourists through time and space. In this study, a database composed of 305 space-time sequences of visitors to Hong Kong was analysed. Data were obtained using global positioning system devices which were distributed among participants. The sequences were aligned using ClustalG, a sequence alignment computer program. The analysis resulted in the identification of various classifications of tourists in Hong Kong based on their time-space patterns.